Preservation management in university libraries in Southern Nigeria (2015)
Information resources in university libraries are susceptible to degradation, deterioration and destruction due to factors such as unfavourable temperature and relative humidity, activities of biological agents, theft and mutilation, mishandling and disasters. Forestalling the situation therefore calls for effective preservation management. University libraries particularly those in tropical zone are faced with acute problem of preservation management. This study, therefore, investigates preservation management of information resources in university libraries in Southern Nigeria. The descriptive research design was adopted for the study. Purposive sampling technique was used to select 24 out of the 33 university libraries in the Southern Nigeria. A self designed questionnaire was used to collect data for the study. Theft and mutilation, unauthorised access to information on computers, mishandling of library materials and deterioration by photocopying were the major threats to information material. Periodic fumigation, binding and repair of information materials and library security were the popular preservation measures available in the university libraries. Challenges facing university libraries in their preservation efforts include lack of electricity to power preservation facilities and equipment, inadequate funding and lack of preservation policy and strategies. The study recommended adequate security measures, adequate funding, provision of uninterrupted power supply and formulation of preservation policy to aid effective preservation management.